Cell Migration Dynamics: High‐Content Analysis of Cell Migration Dynamics within a Micropatterned Screening Platform (Adv. Biosys. 8/2019). Issue 8 (14th August 2019) - Almeida, Filipe V.; Gammon, Luke; Laly, Ana C.; Pundel, Oscar J.; Bishop, Cleo L.; Connelly, John T.
Abstract : In article number 1900011, John T. Connelly and co‐workers report the development of a high‐content screening platform using micro‐patterned and dynamically adhesive substrates. This system is then used to uncover novel epigenetic regulators of keratinocyte migration.